Facile production of chlorophyllides using recombinant CrCLH1 and their cytotoxicity towards multidrug resistant breast cancer cell lines. - Yi-Ping Hsiang; Yi-Ting Wang; Keng-Shiang Huang; Ting-Yu Huang; Mi-Hsueh Tai; Yu-Mei Lin; Chih-Hui Yang; Jei-Fu Shaw (PLoS ONE)
The purity of chlorophylls plays one of the key role for the production of chlorophyllides. We have designed a facile method for chlorophyll purification by twice solvent extraction. Twice extraction causes the loss of chlorophylls, but the purity of total chlorophylls can be enhanced 182%. Then, the purified chlorophylls can be converted to relatively pure chlorophyllides facilely. The results show that higher purity of chlorophyllides could be obtained when purified chlorophylls (ethanol-hexane extract) was used as starting materials than that of crude chlorophylls (ethanol-only extract). In biocompatibility test, the results showed that the prepared chlorophyllides can be applied as biomaterials. When the prepared chlorophyllides were applied to anticancer tests, they were active both in MCF7 and MDA-MB-231 (multidrug resistant breast cancer cells) cell lines. In addition, the results suggested that the prepared chlorophyllides could be a potential candidate of combination therapy with doxorubicin to breast cancers.